Potret Pelaporan SPT Tahunan melalui E-Filing pada Masa Pandemi Covid-19 - Khy'sh Nusri Leapatra Chamalinda; Fariyana Kusumawati (InFestasi, 2021)
This study aims to describe and explore the annual SPT reporting service for individual taxpayers through e-filing at KPP Pratama Bangkalan with tax volunteers during the Covid-19 pandemic, as well as public responses in this case individual taxpayers regarding SPT reporting services. Annual individual taxpayers through e-filing at KPP Pratama Bangkalan during the Covid-19 pandemic. The method in this research is qualitative with a case study approach. The results of the study indicate that the preparation and implementation of the annual tax return reporting service through e-filing during the covid-19 pandemic has gone very well. Annual SPT reporting services during the pandemic are carried out through virtual Integrated Service Places (TPT). Various preparations for the implementation of SPT reporting services have been carried out, both by KPP Pratama Bangkalan and tax volunteers. In the process of SPT reporting services, they still face various obstacles. Various efforts have been made, so that this virtual TPT service can run optimally. In addition, the response of taxpayers to KPP services is that it has been going well. Taxpayers who report their Annual SPT are served as much as possible even though they are virtual. Penelitian ini bertujuan untuk bertujuan untuk menggambarkan serta mengeksplorasi tentang pelayanan pelaporan SPT Tahunan wajib pajak orang pribadi melalui e-filing pada KPP Pratama Bangkalan bersama relawan pajak di masa pandemi Covid-19, serta tanggapan masyarakat dalam hal ini wajib pajak orang pribadi mengenai pelayanan pelaporan SPT Tahunan wajib pajak orang pribadi melalui e-filing pada KPP Pratama Bangkalan di masa pandemi Covid-19. Metode dalam penelitian ini adalah kualitatif dengan pendekatan studi kasus. Hasil penelitian menunjukkan bahwa persiapan hingga pelaksanaan pelayanan pelaporan SPT Tahunan wajib pajak melalui e-filing di masa pandemi covid-19 sudah berjalan sangat baik. Pelayanan pelaporan SPT Tahunan pada masa pandemi dilaksanakan melalui Tempat Pelayanan Terpadu (TPT) virtual. Berbagai persiapan untuk pelaksanaan pelayanan pelaporan SPT telah dilakukan, baik oleh KPP Pratama Bangkalan maupun relawan pajak. Dalam proses pelayanan pelaporan SPT, masih menghadapi berbagai hambatan. Berbagai upaya telah dilakukan, agar pelayanan TPT virtual ini dapat berjalan maksimal. Selain itu, tanggapan wajib pajak terhadap pelayanan KPP yaitu sudah berjalan baik. Wajib pajak yang melaporkan SPT Tahunan dilayani semaksimal mungkin walaupun secara virual.